Temperature effect of metastable atom desorption from solid Ne by low-energy electron impact - Kato, Haruaki; Tachibana, Takayuki; Hirayama, Takato (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
We study the desorption of metastable atoms induced by electronic transitions in solid Ne by low energy electron impact. Time-of-flight spectra and the angular distribution of metastable atoms desorbed from the surface of an annealed sample show increased kinetic energy, higher signal intensity, and a narrower angular distribution compared with those measured using an unannealed sample. These results are explained by considering the sample’s surface conditions in the framework of the cavity ejection mechanism. Our results for annealed solid Ne show that when the sample temperature increases from 5 to 7 K, the width of the angular distribution increases by about 10%. A simple trajectory calculation qualitatively reproduces our experimental results.